STUDI ANALISIS : KESALAHAN MENYELESAIKAN SOAL CERITA PERSAMAAN DAN PERTIDAKSAMAAN LINEAR SATU VARIABEL - Bunga Permaganti; Luvy Sylviana Zanthy (IKIP Siliwangi, 2023)
This study aims to describe the various errors made by students in solving story problems on the material of linear equations and inequalities of one variable. This study uses data analysis techniques, namely a method in processing data into information. The types of error indicators used are errors according to Newman. The subjects of the study were eighth grade students of SMPN 03 Gununghalu. Data collection used written test and interview methods. Based on the results, there were several errors made by the subject, namely the subject made an error in capturing the information contained in the story questions so that the subject had difficulty in completing the next process, based on these errors the subject was also unable to change the problem into a mathematical model and did not write a conclusion. of the answer.